2009
DOI: 10.1590/s1413-35552009005000020
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento das reservas de glicogênio no músculo desnervado de ratas tratadas com diferentes doses de estrógeno

Abstract: Objective: To evaluate the action of estrogen on the glycogen profile of denervated skeletal muscle in female rats. Methods: The animals were divided into six experimental groups (n=6): control; denervated for 15 days; denervated and treated with estrogen at a concentration of 20µg/weight/day; denervated and treated with estrogen at a concentration of 40µg/weight/day; denervated and treated with estrogen at a concentration of 80µg/weight/day; and denervated and treated with estrogen at a concentration of 160µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In animal models, estrogen has been shown to promote lipolysis and increase fatty acid availability, while decreasing the rate of gluconeogenesis and sparing muscle and liver glycogen use [ 6 ] . Estrogen modulates positively the muscle glycogen content in rats [ 37 ] . Thus, under situations of menopause or ovariectomy the concentration of glycogen may be impaired.…”
Section: Resistance Training and Glycogen Content In Ovariectomized Ratsmentioning
confidence: 97%
See 1 more Smart Citation
“…In animal models, estrogen has been shown to promote lipolysis and increase fatty acid availability, while decreasing the rate of gluconeogenesis and sparing muscle and liver glycogen use [ 6 ] . Estrogen modulates positively the muscle glycogen content in rats [ 37 ] . Thus, under situations of menopause or ovariectomy the concentration of glycogen may be impaired.…”
Section: Resistance Training and Glycogen Content In Ovariectomized Ratsmentioning
confidence: 97%
“…However, the above mentioned studies are targeted on fat metabolism, while the eff ects of ovariectomy associated with resistance exercise on liver and skeletal muscle glycogen content have not been investigated. Severi et al [ 37 ] studied the infl uence of estrogen on muscle glycogen content of denervated rats. The results revealed that estrogen appears to positively modulate the muscle glycogen content in denervated rats.…”
mentioning
confidence: 99%